Digital libraries : (Springer, 2006)
This book constitutes the refereed proceedings of the 9th International Conference on Asian Digital Libraries, ICADL 2006, held in Kyoto, Japan in November 2006. It includes 46 revised full papers, 14 revised short papers, and 6 poster papers presented together with 3 keynote and invited papers which were carefully reviewed and selected from a total of 170 submissions. The topics covered by the papers include information extraction, information retrieval, metadata, architectures for digital libraries and archives, ontologies, information seeking, cultural heritage and e-learning. In addition there are 6 papers on national and regional projects on digital libraries and archives (Editorial Reviews)